2017
DOI: 10.2174/1871520616666160826150659
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds A Weapon to Ameliorate Breast Cancer Cells: A Review

Abstract: Breast cancer is the heterogeneous disease and leading cause of death in women, worldwide. It is generally caused by the perturbation of various signaling pathways responsible for cell apoptosis. Due to genetic variability, different signaling pathways are disrupted in different breast cancer patients; so, to overcome this multifaceted condition, the personalized treatment is preferred. Since, various potential targets exist in breast cancer cells; it raised the need of new prospective of lead compounds. A lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In recent years, many naturally occurring compounds commonly present in the diet have gained considerable attention as antitumor agents [13,14]. In this regard, Resveratrol (3,5,4′-trihydroxy-stilbene) (RSV), a phytoalexin found in grapes, has been shown to exert preventive and antiproliferative effects against various types of cancer [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many naturally occurring compounds commonly present in the diet have gained considerable attention as antitumor agents [13,14]. In this regard, Resveratrol (3,5,4′-trihydroxy-stilbene) (RSV), a phytoalexin found in grapes, has been shown to exert preventive and antiproliferative effects against various types of cancer [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several agents with the chemopreventive or chemotherapeutic activity have been isolated from natural products for the treatment of various diseases, including cancer. 40 Accumulating evidence has demonstrated that some of the secondary metabolites from Streptomyces sp. not only act as the antibiotics, but also exhibit anti-tumor, anti-inflammatory, and anti-drug-resistant activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer patients seek for alternative therapies, mostly herbal remedies, as supportive care during cancer treatment, although the evidence of effectiveness is very limited (Greenlee et al 2017). Moreover, phytochemicals are frequently examined for search of new bioactive molecules as well as potential adjuvants in conventional anticancer therapies with numerous examples in the recent literature in our Journal and elsewhere (Newman & Cragg, ; Thakur & Ahirwar, ; Tariq et al, ; Liao, Apaya, & Shyur, ; Bae et al, ; Lin, Gong, Song, & Cui, ; Pagano, Romano, Izzo, & Borrelli, ; Marian, ; Lukong, Ogunbolude, & Kamdem, Salehi et al, ; Erices, Torres, Niechi, Bernales, & Quezada, ; Hsiao, Lin, Wang, Hsin, & Yang, ).…”
mentioning
confidence: 99%